'Healthy organisations': developing the self-managing employee. (2016) - Maravelias, Christian; Holmqvist, Mikael
This paper analyses literature and studies of work place health promotion. It draws on human capital theory to develop the thesis that over and above its ambition of furthering employees' bio-medical health, work place health promotion seeks to make up employees that are able to self-manage their lifestyles and selves as human capital. As such, the paper suggests, work place health promotion emerges as an important source of authority and power in contemporary working life, which has largely been overlooked by the majority of studies of organisational health. While the ambition to further employees' health is basically positive, the paper suggests that WHP is still a potentially precarious activity because it tends towards subordinating not only work, but also life in general to principles of management and performance.